Tendencies in the development of minor place names in the village Otročiněves (with regard to the communication variability of these names) - Klimtová, Barbora (Geographical names in physical space, 2016)
This paper highlights some of the tendencies in the development of minor place names (anoiconyms) in the village Otročiněves (Central Bohemia). The contemporary forms of names have been collected in a direct field research. After the introduction of the criteria for the research, the article focuses on the confrontation of name forms within the set of newly collected anoiconyms, but also on comparison with minor place names excerpted from older sources – from the collection for the Dictionary of Minor Place Names in Bohemia and from the Theresian land register. Thus the article attempts not only to analyze changes in the subset of the Czech anoiconymic system over time, but also to study changes of extralinguistic nature. Anoiconyms will be monitored in their usage in communication as well as in their relation to literary Czech. The attention is also paid to the usage of names in question in different social groups.